2006
DOI: 10.1111/j.1467-9280.2006.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control in Children

Abstract: The development of cognitive control and its relationship to overcoming Stroop interference was assessed in a sample (N = 65) of elementary school children. Subjects alternately performed Stroop color naming trials and word reading trials. In separate blocks, the colored Stroop items were noncolor words (incongruent condition) or rows of asterisks (neutral condition). Younger children showed both larger Stroop interference and a greater slowing of word reading in the incongruent condition. We conducted an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 26 publications
7
52
0
Order By: Relevance
“…However, results similar to ours were obtained by Lamers et al (2010) and Pratte et al (2010). Bub et al (2006) obtained evidence suggesting that younger children (7-9 years) engage in stronger inhibition than older children (9 -11 years) in a vocal Stroop task. Perhaps participants do not need to strongly suppress word-reading when they grow older, as is suggested by our results for adult participants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, results similar to ours were obtained by Lamers et al (2010) and Pratte et al (2010). Bub et al (2006) obtained evidence suggesting that younger children (7-9 years) engage in stronger inhibition than older children (9 -11 years) in a vocal Stroop task. Perhaps participants do not need to strongly suppress word-reading when they grow older, as is suggested by our results for adult participants.…”
Section: Discussionsupporting
confidence: 88%
“…But as described above, whereas some earlier studies (e.g., Bub et al, 2006) found evidence for the involvement of selective inhibition in the Stroop task, others did not (e.g., Soutschek et al, 2013). The latter studies and the present findings suggest that successful Stroop task performance might depend on other control abilities than selective inhibition (see Roelofs, 2003).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…slope between the last two bins) provides the most sensitive metric of the proficiency of inhibitory control over conflicting motor impulses, an assertion supported empirically across several studies using both non-clinical and clinical populations (Burle et al, 2002; Ridderinkhof et al, 2005; Bub et al, 2006; Wijnen and Ridderinkhof, 2007; Wylie et al, 2009a, b, 2010a, b, 2005; for review, see van den Wildenberg et al, 2010). …”
Section: Methodsmentioning
confidence: 82%
“…According to the activation–suppression hypothesis, the engagement and build up of selective suppression of direct response activation can be observed by plotting the interference effect as a function of the entire RT distribution (i.e., delta plots). In particular, the modulation of the interference effect at the slowest segments of the distribution, where inhibition is expected to be fully engaged, is sensitive to group differences in the efficiency of inhibitory control (Bub, Masson, & Lalonde, 2006; Ridderinkhof, Scheres, Oosterlaan, & Sergeant, 2005; Wylie, Ridderinkhof, Eckerle, & Manning, 2007). Guided by this framework and the proposed role of the basal ganglia during action selection, we predicted that PD patients would show reduced selective suppression of incongruent responses when instructions emphasized speed of responding.…”
Section: Introductionmentioning
confidence: 99%